STUDI FENOLOGI PERBUNGAAN Lilium longiflorum Thunb. - Deswiniyanti, Ni Wayan; Astarini, Ida Ayu; Puspawati, Ni Made (Metamorfosa: Journal of Biological Sciences, 2013)
Lily (Lilium longiflorum Thunb.) was known as ornamental plants, especially as cut flower. Lily varieties in Indonesia are still lacking and the price is quite expensive but demand of lily is increased steadily. The first step for successful plant breeding is understanding phenophysiology of the plants, in particular flowering phenology. The aim of this research is to provide information on flowering lily phenology, to be a basic knowledge in improving for planning plant breeding programs. In this research, plants were observed from bud initiation until fruit production (phase F0-F4). Additional morphologies observed such as: high plant, leaf shape and color, shape and type of root or bulb. Result shows that period of phase F0-F3 of sampled lily is 52 days. The plant height of lily is about 50-150 cm, has elongated single lancet leaf shape, green leaf, bulbs, and has fiberous root.
Keywords: phenology, liliaceae, cut flower, plant breeding.